Упростить выражение 1/2 (a+b+c) (a+b+c) - ab

+3
Ответы (1)
  1. 13 апреля, 07:59
    0
    1 / 2 * (a + b + c) * (a + b + c) - a * b

    пусть (a + b + c) = t, тогда

    1 / 2 * t * t - a * b = 1 / 2 * t в степени 1 * t в степени 1 - a * b = 1 / 2 * t (1 + 1) - а * b = 1 / 2 * t в квадрате - a * b = 1 / 2 * (a + b + c) в квадрате - a * b

    в итоге получили 1 / 2 * (a + b + c) * (a + b + c) - a * b = 1 / 2 * (a + b + c) в квадрате - a * b

    ответ: 1 / 2 * (a + b + c) * (a + b + c) - a * b = 1 / 2 * (a + b + c) в квадрате - a * b
Знаешь ответ на этот вопрос?